2019
DOI: 10.3892/etm.2019.7680
|View full text |Cite
|
Sign up to set email alerts
|

β‑catenin regulates effects of miR‑24 on the viability and autophagy of glioma cells

Abstract: Mutations of the β-catenin gene are common in various cancer types. MicroRNA (miR)-24 suppresses gene expression during the cell cycle. However, the effects of miR-24 on the cell viability and autophagy of glioma cells, and how these biological processes are regulated by β-catenin are largely unclear. The current study aimed to investigate the role of β-catenin in regulating the effects of miR-24 on the cell viability and autophagy of glioma cells. The expression levels of microtubule-associated proteins 1A/1B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Therefore, other therapeutic approaches against GBM are aiming to induce autophagy through mTOR inhibition. The first line of mTOR inhibitors, however, were able to block only mTOCR1 activity (183). As seen throughout this review, mTORC2 is involved with GBM invasion and could inhibit CMA.…”
Section: Crosstalk Between Autophagy Epithelial-mesenchymal Transitimentioning
confidence: 91%
“…Therefore, other therapeutic approaches against GBM are aiming to induce autophagy through mTOR inhibition. The first line of mTOR inhibitors, however, were able to block only mTOCR1 activity (183). As seen throughout this review, mTORC2 is involved with GBM invasion and could inhibit CMA.…”
Section: Crosstalk Between Autophagy Epithelial-mesenchymal Transitimentioning
confidence: 91%
“…Most recently, Zappavigna et al (2019) reported that EA0100C red, a hydroquinone-based derivative, elicited autophagy through activation of a ROS-dependent unfolded protein response in GBM, which may be the basis of its antitumor effects. A recent study showed that the antitumor activity of miR-24 was due, at least in part, to effects on glioma cell autophagy and viability (Chen et al, 2019). In addition to escitalopram oxalate, other psychiatric medications, including clozapine and fluphenazine, have been recently reported to induce autophagic cell death (Shen et al, 2016; Kim et al, 2018b).…”
Section: Potential Molecular Mechanisms Underlying the Anticancer Promentioning
confidence: 99%
“…In primary malignant brain tumor glioblastoma, miR-23 was downregulated along with its target ATP5A1 or ATP5B high expression by miRNA microarray [ 69 ]. However, miR-24 was demonstrated to favor proliferation, invasion and viability of glioma cells by targeting ST7L and activating β-catenin/Tcf-4 signaling axis [ 70 , 71 ]. An integrated statistic analysis authenticated that miR-23a collaborating with miR-27a could promote PNI in PDAC [ 46 ].…”
Section: Mirna Alterations Associated With Pnimentioning
confidence: 99%